Preparation of vermicompost from neem leaf and oil palm empty fruit bunch and evaluation of its bioactivity on fruit fly Bactrocera dorsalis hendel - Loh, Khye Er (2013)
Bactrocera dorsalis (Diptera: Tephritidae) is one of the major obstacles in the development of fruit industry in Malaysia. The pupation of B. dorsalis in the ground provides the possibility of controlling them using vermicompost, which is commonly applied as soil dressing around the base of plants. The palm oil industry generates empty fruit bunch (EFB) in large quantity as by-product, which need to be optimally exploited to obtain maximum benefits from their uses. Vermicomposting the mixture of EFB and neem (Azadirachta indica) leaves, with the latter known to have pesticidal value is of great interest. Therefore, vermicomposting of different ratio of EFB and neem leaves using the earthworm, Eudrilus eugeniae was conducted. The optimal mixture of neem leaf-empty fruit bunch for vermicomposting was determined. The earthworm performance, chemical and biological properties of different mixture composition were compared. This study found that vermicompost with the ratio of 10% neem leaves: 70% EFB: 20% cow dung (10%N:70%EFB:20%CD) showed the best earthworm performance and vermicompost quality. The study was then carried on by using 10%N:70%EFB:20%CD vermicompost and 10%N:90%EFB vermicompost, as cow dung control. The evaluation on the vermicompost in controlling B. dorsalis was conducted. The vermicomposts resulted in 10.67-12.80% reduction in adult emergence and 3.47-4.67% abnormal wing formation, significantly higher than the control. The dichloromethane fraction from vermicompost extract was shown to be the most bioactive fraction. Then, the characterization of B. dorsalis emergence inhibitor from vermicompost using metabolomics approach was conducted using the dichloromethane fraction. The classification of the 10%N:90%EFB vermicompost and its raw materials (neem leaf and EFB) were obtained by means of principal component analysis (PCA). The vermicompost, neem leaves and EFB were clustered into three different groups according to their proton nuclear magnetic resonance (1H NMR) characteristics. The NMR profiles of the chemical constituents of the samples were correlated to the inhibition activity of the fruit flies using partial least square (PLS), wherein neem leaf was shown to be the major inhibitor. Based on NMR-metabolomics approach, the metabolites of the neem leaf responsible for the activity were identified as azadirachtin and salannin. In conclusion, neem leaf-empty fruit bunch-based vermicompost has the potential as biofertilizer-cum-biopesticide in controlling B. dorsalis population.